2020
DOI: 10.1111/wvn.12469
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Work Engagement Among Registered Nurses: Implications for Evidence‐Based Action

Abstract: Background: Previous studies evaluating work engagement of nurses revealed work-related factors and nurse demographics affecting work engagement. Low work engagement yields a decrease in productivity, high turnover, loss of revenue, and, most importantly, patient safety concerns. Aim: To investigate the relationship between nurse-related and work-related variables associated with work engagement and provide a model that explains work engagement. Method: This study employed an observational, cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
2
30
1
1
Order By: Relevance
“…The work engagement level was also significantly lower than that observed in the group of junior nurses and head nurses (Wang, Yang, et al, 2019), but higher than that in the group of nurses working in COVID-19 prevention (Giménez-Espert et al, 2020). Among the three dimensions, the vigour scores were the highest, which indicates that nurses working in nursing homes approach their work with exuberant energy and good men- (Pericak et al, 2020).…”
Section: As Shown Inmentioning
confidence: 60%
See 1 more Smart Citation
“…The work engagement level was also significantly lower than that observed in the group of junior nurses and head nurses (Wang, Yang, et al, 2019), but higher than that in the group of nurses working in COVID-19 prevention (Giménez-Espert et al, 2020). Among the three dimensions, the vigour scores were the highest, which indicates that nurses working in nursing homes approach their work with exuberant energy and good men- (Pericak et al, 2020).…”
Section: As Shown Inmentioning
confidence: 60%
“…Advancing age was associated with lower dedication level at work. A study conducted in United States also demonstrated the effect of age on work engagement among registered nurses (Pericak et al, 2020). Age is often considered as the most important demographic factor that affects the nurses' work engagement.…”
Section: Discussionmentioning
confidence: 95%
“…The findings revealed that the participants’ evaluation of their practical skills, professional knowledge, and satisfaction with their professional activities had affected their LOP. In line with this finding, a study revealed that the self-evaluation of professional abilities significantly affected professional engagement [ 54 ]. Another study also showed a significant relationship between clinical self-efficacy and clinical belongingness [ 55 ].…”
Section: Discussionmentioning
confidence: 64%
“…Despite the unique context, findings of negative correlations between work satisfaction and burnout, burnout and intention to stay, and burnout and work engagement, and positive correlations between work satisfaction and intention to stay are all consistent with previous nursing research. [24] , [25] Multiple correlations between the study dimensions highlight the complex issues for implementing technology with a nursing workforce. Understanding the complex interplay of well-being, work engagement, motivation to use technology and experience using EMR can assist with targeted strategies to minimise the negative impacts of major change associated with technology implementation on the nursing workforce.…”
Section: Discussionmentioning
confidence: 99%